Penerapan Prinsip-Prinsip Teori Belajar Humanistik dalam Lingkungan Sekolah Dasar: Kajian Psikologi Pendidikan di UPT SDN 14 Lunang - Dewi Fitriana; Gusmal Hendra; Mujiati; Novi Zaini; Kartini; Halimatul Mahmudah (STKIP Subang, 2025)
This study aims to examine the application of humanistic learning theory principles in an elementary school setting, focusing on UPT SDN 14 Lunang. A qualitative approach with a descriptive–interpretative design was employed to explore teachers’ psychological processes in implementing humanistic learning. The participants were classroom teachers selected through purposive sampling. Data were collected through in-depth interviews, non-participant observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the application of humanistic learning theory at UPT SDN 14 Lunang is reflected in the implementation of confluent education, open education, cooperative learning, and social-based learning, which contribute to creating a psychologically safe learning environment, fostering students’ emotional engagement, and strengthening social interactions. These results suggest that humanistic learning theory can be effectively actualized in elementary schools as a psychological educational approach that supports meaningful learning and holistic student development.